1998
DOI: 10.1021/jp973338x
|View full text |Cite
|
Sign up to set email alerts
|

Proton Tunneling in the Loss of Hydrogen Bromide from Energy-Selected Gas-Phase 2-Bromobutane Cations

Abstract: The dissociation dynamics of energy-selected 2-bromobutane ions has been investigated by photoelectron photoion coincidence (PEPICO). The data were collected with a conventional gas discharge light source at the University of North Carolina and at the SuperACO synchrotron storage ring of LURE in Orsay, France. The 2-bromobutane ion dissociates via Br and HBr loss within 0.3 eV of the ionization limit. The Br loss channel produces the sec-butyl ion C4H9 + via a simple bond cleavage and is found to proceed at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
24
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
8
24
0
Order By: Relevance
“…In that case, the rates are often dominated by tunnelling through these barriers, 26,27 which offer opportunities to model tunnelling steps. Because of the large ion neutral attractive potentials, ionic reactions provide excellent examples of dissociation events with no barriers.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the rates are often dominated by tunnelling through these barriers, 26,27 which offer opportunities to model tunnelling steps. Because of the large ion neutral attractive potentials, ionic reactions provide excellent examples of dissociation events with no barriers.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several groups published a collaborative work on the dissociation of 2-Bromobutane ions [18]. They found that Br loss channel proceeds at a fast rate, while the HBr loss is slow and tunneling is again involved in the reaction.…”
Section: Tof and Energy Dependence Measurementsmentioning
confidence: 99%
“…Underestimation of the barrier by a few tenth of eV is possible. 2,[7][8][9] We have taken 0.64 eV as the best estimate of the classical barrier for the ratedetermining step compatible with the PEPICO data (see below). The tunneling-corrected RRKM rate-energy relation calculated with this critical energy is shown in Fig 5. According to the calculated rate-energy relation, observation of the dissociation on microsecond time scales both in the previous PEPICO and current MIKES experiments means that the reaction occurring at 0.1-0.2 eV below the threshold via quantum mechanical tunneling was detected.…”
Section: Quantum Mechanical Tunneling In the Production Of Cpmentioning
confidence: 99%
“…This has often been invoked to explain some of the unusual kinetic phenomena observed experimentally. [1][2][3][4][5][6][7][8][9] As is well known, the tunneling effect may appear prominently for reactions involving H-atom transfer. Miller reported an algorithm to evaluate the tunneling-corrected transition state rate constant using the curvature at the transition state obtained from the quantum chemical calculation.…”
mentioning
confidence: 96%